FDG-PET or PET/CT in Fever of Unknown Origin: The Diagnostic Role of Underlying Primary Disease. (14th February 2011) - Ergül, Nurhan; Çermik, Tevfik Fikret
Abstract : Fever of unknown origin (FUO) is generally defined as a fever greater than 38.3°C on several occasions during a period longer than 3 weeks for which the etiology behind cannot be diagnosed at the end of at least 1 week hospital stay. Conventional diagnostic methods are still not adequate to reveal underlying reason in approximately 50% of patients with FUO. In patients with certain diagnosis, three major categories are infections, malignancies, and noninfectious inflammatory diseases. Fluoro-18-fluoro-2-deoxy-D-glucose (FDG) is a structural analog of 2-deoxyglucose and accumulates in malignant tissues but also at sites of infection and inflammation. For this reason, FDG PET or PET/CT has great advantage in understanding of underlying pathology in assessment of FUO. However, till today, there are limited studies about the role of FDG PET or PET/CT in evaluation of FUO. In this paper, the impact of FDG PET or PET/CT in the diagnostic work-up of FUO is described by data obtained from literature review.